Use of [18F]FDG Positron Emission Tomography to Monitor the Development of Cardiac Allograft Rejection. Issue 9 (September 2015) - Daly, Kevin P.; Dearling, Jason L. J.; Seto, Tatsuichiro; Dunning, Patricia; Fahey, Frederic; Packard, Alan B.; Briscoe, David M.
<x xml:space="preserve">Abstract</x> Background Positron emission tomography (PET) has the potential to be a specific, sensitive and quantitative diagnostic test for transplant rejection. To test this hypothesis, we evaluated 18F-labeled fluorodeoxyglucose ([18F]FDG) and 13N-labeled ammonia ([13N]NH3) small animal PET imaging in a well-established murine cardiac rejection model. Methods Heterotopic transplants were performed using minor major histocompatibility complex-mismatched B6.C-H2bm12 donor hearts in C57BL/6(H-2b) recipients. C57BL/6 donor hearts into C57BL/6 recipients served as isograft controls. [18F]FDG PET imaging was performed weekly between posttransplant days 7 and 42, and the percent injected dose was computed for each graft. [13N]NH3 imaging was performed to evaluate myocardial perfusion. Results There was a significant increase in [18F]FDG uptake in allografts from day 14 to day 21 (1.6% to 5.2%; P < 0.001) and uptake in allografts was significantly increased on posttransplant days 21 (5.2% vs 0.9%; P = 0.005) and 28 (4.8% vs 0.9%; P = 0.006) compared to isograft controls. Furthermore, [18F]FDG uptake correlated with an increase in rejection grade within allografts between days 14 and 28 after transplantation. Finally, the uptake of [13N]NH3 was significantly lower relative to the native heart in allografts with chronic vasculopathy compared to isograft controls on day 28 (P = 0.01). Conclusions PET imaging with [18F]FDG can be used after transplantation to monitor the evolution of rejection. Decreased uptake of [13N]NH3 in rejecting allografts may be reflective of decreased myocardial blood flow. These data suggest that combined [18F]FDG and [13N]NH3 PET imaging could be used as a noninvasive, quantitative technique for serial monitoring of allograft rejection and has potential application in human transplant recipients.